2011
DOI: 10.1002/app.35614
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of gamma irradiation on electrical and mechanical properties of epoxy nanocomposites

Abstract: In this work, the influences of gamma irradiation on the electrical and mechanical properties of the epoxy nanocomposites were studied. The exfoliation characteristics of epoxy nanocomposite material analyzed through TEM studies. It is shown that the impact and flexural strength of the material is high with epoxy nanocomposites and gets reduced with the gamma‐irradiated specimen. The AC breakdown strength of the epoxy nanocomposites is high compared with the base epoxy resin. It is also observed that a reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…With the addition of nanoparticle, the charge transport behaviour changes, which is in agreement with previous studies [6,18]. The depth of traps for nanocomposite is deeper than that for ER samples.…”
Section: Charge Transport Behavioursupporting
confidence: 91%
See 3 more Smart Citations
“…With the addition of nanoparticle, the charge transport behaviour changes, which is in agreement with previous studies [6,18]. The depth of traps for nanocomposite is deeper than that for ER samples.…”
Section: Charge Transport Behavioursupporting
confidence: 91%
“…The structure changes of ER and its nanocomposites before and after acid/alkaline corrosion at different temperatures are shown in Figures 3-5. The corrosion mechanism has been mainly studied, rather than the influence of nanoparticle content on ER-based samples in physical and chemical structures, which has been discussed in previous studies [6,18]. In order to clearly show the effect of chemical corrosion on the structure of samples, the typical results are presented in this section.…”
Section: Structure Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noticed that with varying dosage rate, the average amount of accumulated charge differs because of the irradiation induced mechanisms. Karpagam et al studied the impact of gamma irradiation on epoxy–clay nanocomposites and observed less space charge density with gamma‐irradiated specimens [28].…”
Section: Resultsmentioning
confidence: 99%